ОЦЕНКА НАКОПЛЕНИЯ ТОКСИЧНЫХ ЭЛЕМЕНТОВ И РАДИОНУКЛИДОВ В ПРОДУКЦИИ ЖИВОТНОВОДСТВА СЕВЕРНОГО, ЦЕНТРАЛЬНОГО И ВОСТОЧНОГО КАЗАХСТАНА. - Ж. Адильбеков; Р. Мустафина; Ю. Балджи; В. Нурумбетова; А. Серикова; Ш. Сулейменов; Б. Кадралиева (Animal Health and Biosafety, 2026)
Inadequate study of environmental pollution and production of animal origin with man-made contaminants in ecologically disadvantaged regions of Kazakhstan necessitates a complex assessment of their safety. The purpose of the work was to estimate the level of contamination by toxic elements and radionuclides of animal husbandry products in technogenically dangerous regions of Eastern, Northern and Central Kazakhstan. Research was conducted from August 2024 to September 2025 in Abai, Akmola and Karaganda regions. Samples of meat, milk and dairy products were taken at checkpoints in the Abai region, adjacent to the former Semipalatinsk nuclear test site, as well as in the regions of Akmola and Karaganda regions, located near large industrial enterprises. A total of 384 samples of livestock products were investigated. The content of toxic elements was determined by the analyzer EXPEC 6500, radionuclides by the multi-channel gamma spectrometer CANBERRA. Statistical data processing was performed using IBM SPSS Statistics v25. Exceeding the maximum allowable concentrations of heavy metals was revealed in the studied samples. The most pronounced contamination was found in the Karaganda region: the high content of lead, cadmium and zinc was noted in the horse, and copper in the beef. In the Akmola region, an excess of copper and, in some cases, cadmium, including chicken meat, was registered. Cadmium was the main pollutant in meat production in the Abai region. An excess of cadmium in curd and copper in milk has been established in the milk production of Akmola region. An excess of lead and cadmium in cottage cheese, as well as cadmium in milk, was revealed in the Karaganda region. In the Abai region, high lead content was noted in milk samples. Exceeding the maximum allowable concentrations of radionuclides has not been detected. The obtained data show that technogenic loading of certain territories affects the safety of animal husbandry production and requires regular monitoring of heavy metals and radionuclides in meat, milk and dairy products. Special attention should be paid to regions located near industrial facilities and territories with historical radiation exposure. Such an approach will allow timely detection of risks and prevention of entry of contaminated products into the food chain.